EKSISTENSI LEMBAGA KEUANGAN MIKRO DALAM PENINGKATAN AKSESIBILITAS PELAKU USAHA PERTANIAN PADA SUMBER PERMODALAN DI PEDESAAN - Yekti, Ananti; Sulastyah, Amie (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2009)
The study was conducted to identify: 1) the variety of farmers and sources of funds in the agriculture sector; 2) credit sources accessible to farmers; 3) the intensity of relations and effectiveness of fund utilization; 4) the scheme characteristics/credit models preferred by farmers. The study was conducted from March to August 2009, in Piyungan, Yogyakarta. Data was analyzed descriptively. The study result showed that 100% of the rural community have taken loans from informal financing institutions namely Lembaga Keuangan Bukan Bank Bukan Koperasi (Non Bank Non- Cooperatives Financing Institutions), while only 50.2% 126.9% from banks, 20% from cooperatives and 3.3% from mortgage institutions). The total of credit taken ranges from Rp. 150,000 to Rp. 20,000,000. Informal financing institutions provide credits in small amount while bankable provide larger loans. Micro Finance Institutions were more preferred by those who are less bankable and less feasible. The loans were usually utilized to expand existing business (100%), to start other lines of business (30%), to cover the previous business loss (13.3%), and to cover household needs (16,7%).